The Characteristic of Central Serous Chorioretinophaty Patients at Sanglah General Hospital Bali-Indonesia - Lienderi-Wati, N. M.; Budhiastra, P.; -, Ari-Andayani (BALI MEDICAL JOURNAL; Volume 1, Number 2, May-August 2012, 2013)
Objective: to describe characteristics of central serous chorioretinophaty (CSC) patients in Sanglah General Hospital, correlation between visual acuity and foveal thickness before and after oral acetazolamide theraphy, the differences of visual acuity and foveal thickness of CSC’s patients before and after oral acetazolamide theraphy. Methods : This study is a descriptive study, than followed by cross sectional study. Data were collected retrospectively from medical report of CSC patients who came to Sanglah General Hospital during period Januari 1 st 2010 until December 31 st 2011. Results : Central serous chorioretinopathy were found in 22 patients (22 eyes), male predominance (72.7%), majority were in age group 30-40 years (54.55%), and all of cases were unilateral. Most of CSC patients worked as private employees (77.3%). Mean onset patients presented to the hospital was 14.64±5.68 days, with the most common symptom was decreasing vision (86.4%). Mean of follow ups in CSC patients were 64.11±6.15 days. There was correlation between visual acuity and foveal thickness before and after oral acetazolamide theraphy, respectively r=0.76; p=0.001 and r=0.73; p=0.001 (Spearman test). The differences between visual acuity of CSC patients before and after oral acetazolamide theraphy was significant (0.55±0.26 logMAR vs 0.11±0.12 logMAR; p=0.001; Wilcoxon test). The differences between foveal thickness of CSC patients before and after oral acetazolamide theraphy  was also significant (484.23±6.42 vs 258.41±4.21; p=0.001; Wilcoxon test). Conclusions : CSC patients was male predominance, majority in decade 3-4, all of cases were unilateral and most of the patients worked as private employees. There is a strong correlation between visual acuity and foveal thickness before and after oral acetazolamide theraphy. A significant differences found in visual acuity and foveal thickness of CSC’s patients before and after oral acetazolamide theraphy. In this study, the role of oral acetazolamide in clinical resolution improvement of CSC’patients can not be concluded. Further study with control group needed to find it’s role.
Keywords: Central serous chorioretinopathy, neurosensory retina, visual acuity, foveal thickness